Quantitative and semiquantitative estimates of mold exposure in infancy and childhood respiratory health. Issue 4 (19th August 2020) - Cox, Jennie; Ryan, Patrick; Burkle, Jeff; Jandarov, Roman; Mendell, Mark J.; Hershey, Gurjit Khurana; LeMasters, Grace; Reponen, Tiina
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Previous epidemiologic studies of dampness and mold relied on metrics that did not fully assess exposure–response relationships. Our objective was to examine quantitative metrics of dampness and mold during infancy and respiratory health outcomes during childhood. Methods: In-home visits were conducted before age 1 for children in the Cincinnati Childhood Allergy and Air Pollution Study. Respiratory outcomes included age 3 wheeze and age 7 asthma and wheeze. The associations between home exposure and respiratory outcomes were evaluated for 779 children using logistic regression adjusting for household income, neighborhood socioeconomic status, and the presence of pests. Results: Children residing in homes with ≥0.29 m 2 of moisture damage were significantly more likely to have wheezing at age 3 and persistent wheeze through age 7 (adjusted odds ratio [aOR] = 2.2; 95% confidence interval [CI] = 1.0, 4.3 and aOR = 3.2; CI = 1.3, 7.5, respectively). Additionally, homes having ≥0.19 m 2 of mold damage were associated with wheezing at age 3 and early transient wheeze assessed at age 7 (aOR = 2.9; CI = 1.3, 6.4 and aOR = 3.5; CI = 1.5, 8.2, respectively). Mold damage <0.19 m 2 and moisture damage <0.29 m 2 were not associated with health outcomes. Mold and moisture damage were also not associated with asthma. Conclusion: Our data indicate that only the highest categories analyzed for mold (≥0.19 m 2 ) and moisture damage (≥0.29 m 2 ) in homes at age 1 were significantly associated with wheeze at ages 3 and 7; however, data below these levels were too sparse to assess the shape of the relationship or explore potential health-relevant thresholds.